Geochemical and geophysical constrains on the dynamic topography of the Southern African Plateau. (5th October 2017) - Jones, Alan G.; Afonso, Juan Carlos; Fullea, Javier
Abstract: The deep mantle African Superswell is considered to contribute to the topographic uplift of the Southern African Plateau, but dynamic support estimates vary wildly depending on the approach and data used. One reason for these large disparities is that the role of lithospheric structure, key in modulating deep dynamic contributions to elevation, is commonly ignored or oversimplified in convection studies. We use multiple high‐quality geophysical data coupled with xenolith‐based geochemical constraints to compute the isostatic lithospheric contribution to the elevation of the Plateau, facilitating isolation of the current dynamic component from the total observed elevation. We employ a multiobservable stochastic algorithm to invert geoid anomaly, surface‐wave dispersion data, magnetotelluric data, and surface heat flow to predict elevation in a fully thermodynamically and internally‐consistent manner. We find that a compositionally layered 230 ± 7 km thick lithosphere is required to simultaneously fit all four data types, in agreement with abundant independent xenolith evidence. Our stochastic modeling indicates a lithospheric contribution to elevation of the order of 670 m, which implies dynamic support arising from the convecting sublithospheric mantle of ∼650 m. Our results have important implications for the understanding of lithospheric‐deep mantle feedback mechanisms and for calibrating dynamic topography estimates from global convection studies. Plain Language Summary: Is the Kaapvaal Craton too high? Yes is the short answer. Its elevation cannot be sustained by the lithosphere of the craton itself, therefore there must be support from beneath the base of the lithosphere, so‐called dynamic topography. We show through very careful modelling of the Kaapvaal Craton lithosphere that alone it can support an elevation of the order of 670 m, therefore the other approx. 650 m must come from mantle processes beneath the base of the lithosphere. Key Points: Joint stochastic inversion of four distinct geophysical data types for Kaapvaal Craton Geochemical, thermal, and water content constraints applied in final test Infers that there is dynamic support of the order of 650 m